1983
DOI: 10.1017/s0034412500015006
|View full text |Cite
|
Sign up to set email alerts
|

Landscape, Consciousness, and Culture

Abstract: A longstanding but inchoate preoccupation of mine is the geography of religions. How are landscape and religious faith related? In the context of this question, the definition of religion with which I work entails two considerations: first, what landscape features are incorporated into traditional religious symbol systems? I shall make a few observations about this geographic symbology below. Second, what is the existential connection between landscape and personal faith, i.e. between physical land features an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Following Tuan and Wright, other authors have later suggested that religion is directly influenced by the landscape (Gualteri 1983) or could even be considered a geographical phenomenon. For instance, J. Gary Knowles stressed the practical, action-oriented attachment and reverence for particular places in the environment: "geopiety connotes action and notions of responsiveness towards a place that is regarded as sacred" (Knowles 1992, p. 9).…”
Section: Geopiety Nature-related Devotional Titles and The Spiritual ...mentioning
confidence: 99%
“…Following Tuan and Wright, other authors have later suggested that religion is directly influenced by the landscape (Gualteri 1983) or could even be considered a geographical phenomenon. For instance, J. Gary Knowles stressed the practical, action-oriented attachment and reverence for particular places in the environment: "geopiety connotes action and notions of responsiveness towards a place that is regarded as sacred" (Knowles 1992, p. 9).…”
Section: Geopiety Nature-related Devotional Titles and The Spiritual ...mentioning
confidence: 99%
“…Physical and Spatial Aspects: Gualtieri [29] and Mansvelt and Pedroli [30] declared 'place identity' to be the basic physical-human interaction between people and the physical environment. The broad sense of the physical world includes both the physical properties of the settings and the involvements, memories and symbolic meanings.…”
Section: Aspects Of Landscape Identitymentioning
confidence: 99%